2020
DOI: 10.1016/j.cgh.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Colorectal Neoplasia: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND & AIMS:Most colorectal cancers (CRC) arise from colorectal adenomas, yet there is not enough information on global prevalence to inform health care policy. We examined the prevalence of any type of adenomas, advanced adenomas (AADs), and CRC according to age, sex, ethnicity, geographic regions, and anatomic location (proximal vs distal). METHODS:MEDLINE and Embase were searched from their inception through May 1, 2018, to identify population-based, observational studies that reported the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 91 publications
5
40
2
3
Order By: Relevance
“…As a comparison, a recent meta-analysis found a prevalence of colorectal cancer of 0.8% (95% CI, 0.4%-0.7%) in individuals age 50 years and older. 8 High-quality evidence from randomized controlled trials of flexible sigmoidoscopy 9,10 showed that endoscopic screening reduces colorectal cancer incidence and mortality. Indirectly, this suggests that detection of colorectal cancer through endoscopic evaluation of patients with IDA is important, particularly with the ongoing advances in therapy for colorectal cancer and subsequent improvements in survival.…”
Section: Very Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparison, a recent meta-analysis found a prevalence of colorectal cancer of 0.8% (95% CI, 0.4%-0.7%) in individuals age 50 years and older. 8 High-quality evidence from randomized controlled trials of flexible sigmoidoscopy 9,10 showed that endoscopic screening reduces colorectal cancer incidence and mortality. Indirectly, this suggests that detection of colorectal cancer through endoscopic evaluation of patients with IDA is important, particularly with the ongoing advances in therapy for colorectal cancer and subsequent improvements in survival.…”
Section: Very Lowmentioning
confidence: 99%
“…As a comparison, a recent meta-analysis found a prevalence of colorectal cancer of 0.1% (95% CI, 0%-0.1%) in individuals younger than 50 years, but did not estimate incidence separately for men and women. 8 It should also be noted that the incidence of colorectal cancer has increased in younger cohorts recently. 17 We did not find reliable data to define the risk of gastrointestinal malignancy in premenopausal women at different ages or with different degrees of anemia, but the prevalence of either upper or lower gastrointestinal malignancy will decrease with decreasing age in this population.…”
Section: Very Lowmentioning
confidence: 99%
“…However, this is highly unlikely, given that the fall in incidence seen in the flexible sigmoidoscopy screening trials was accompanied by reductions in mortality. 7 In addition, just as North America, Oceania and most European countries, 6 CRC mortality in the 50-74 years age range in Scotland has fallen over time and it is likely that part of this effect can be attributed to early detection and prevention of disease as a result of screening. 16 It is also interesting that we did not observe a fall in CRC mortality in the under 50 years age range, lending further strength to the argument that screening has contributed to this trend.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%
“…3 In a recent analysis of incidence and mortality databases from 39 countries, it was confirmed that countries with the highest HDI had a decrease in CRC incidence, but that incidence of colon and rectal cancers has continued to increase in countries with medium-high HDI, and in younger populations. 6 It has been postulated that screening may be responsible for the reduction in incidence in the group aged over 50 years, especially where this is associated with high rates of large bowel endoscopy, which facilitates the diagnosis and removal of pre-malignant adenomas. 3 Since there is now robust evidence from randomised trials of endoscopic screening that removal of adenoma leads to a reduction in CRC incidence, 7 this is an attractive hypothesis, but one that is difficult to test.…”
mentioning
confidence: 99%
“…A new systematic review and meta-analysis combined 70 primary population-based cross-sectional studies that used colonoscopy for assessing different colorectal neoplastic lesions. This study reported the worldwide prevalence of adenoma, advanced adenoma and CRC as 25.9%, 5.2% and 0.6% in patients older than 50 years, respectively 3 . Brenner et al investigated almost 850,000 colonoscopies of German national screening of CRC.…”
Section: Introductionmentioning
confidence: 77%